Exploring Anger Management Strategies in Addressing Teacher Burnout - Muhammad Hudhel Sidqi; Bakri Muhammad Bakhiet; Febriyanti Ghayatul Qushwa (Journal of Psychological Insight, 2026)
Teacher burnout is frequently accompanied by unmanaged anger that disrupts instructional quality and professional stability. This study aims to analyze the forms of teacher anger, identify anger management strategies applied in classroom settings, and examine their impact on burnout and teaching quality. Using a qualitative case-based approach, data were collected from teachers through in-depth interviews, classroom observations, and document analysis, and were examined using thematic analysis. The findings reveal that anger, manifested in verbal reactions, nonverbal expressions, and internal emotional suppression, is linked to emotional exhaustion. Teachers applied physiological regulation, cognitive reframing, spiritual-reflective practices, and controlled behavioral responses as management strategies. These strategies were associated with reduced emotional exhaustion, improved teacher–student relationships, more conducive classroom climates, and strengthened professional conduct. This study contributes by positioning anger as a specific operational dimension within burnout discourse. The findings imply that structured emotional regulation training should be integrated into teacher professional development programs.